Transmission Opportunities: A New Approach to Improve Quality in V2V Networks - Guerber, Carlos Rafael; Gomes, Eduardo Luis; Pereira Fonseca, Mauro Sérgio; Munaretto, Anelise; Silva, Thiago Henrique (Wireless Communications and Mobile Computing, 2019)
In vehicular ad hoc networks (VANETs), vehicle-to-vehicle (V2V) communication occurs opportunistically due to frequent node mobility and intermittent contact time. In this scenario, the performance evaluation of forwarding protocols by the use of the existing resources in the network is an open challenge, given the different strategies that the routing protocols adopt for choosing the next hop. Through the data analysis of three real taxis’ mobility traces and varying the radio signal range from 50 meters to 1.000 meters, we could contribute to the analysis of the existence of single-radio transmission opportunities and their quantification and classification considering either serial or parallel. Additionally, the inventory analysis of communication resources is done by evaluating the data transmission rate and the beacon overhead impact and by the proposal of a new metric (TOppMi) for the performance evaluation of forwarding protocols. We discuss the impact on forwarding protocols by the appropriate use of this metric, and we show that this metric can be used either for performance evaluation of forwarding protocols or to improve the quality over the consumption of resources in vehicular ad hoc networks. Our metric can obtain the maximum theoretical resource usage independent of the scenario. Either for Rome or San Francisco or Shanghai, as the radio’s signal range increases, the maximum theoretical amount of resources also increases. We could also show that, for the three scenarios, the beacon overhead has an insignificant impact over the total theoretical data inventory available. Furthermore, we classify the vehicles according to the contact time between them.